2018
DOI: 10.1159/000491086
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metformin on the Endometrium of Women with Polycystic Ovary Syndrome

Abstract: Objectives: To investigate the effect of metformin on endometrial receptivity in women with polycystic ovary syndrome (PCOS). Methods: Twenty volunteer women with polycystic ovaries and oligomenorrhea were prospectively investigated. All women were treated with exogenous estradiol and progesterone to simulate a normal menstrual cycle (28-day duration) after GnRH-induced pituitary desensitization. Ten of the women received no other medication (group A, control), while the remaining 10 received metformin (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Numerous studies have illustrated that infertile PCOS patients present the impairment of endometrial receptivity and were vulnerable to undergo recurrent pregnancy loss, premature labour and fetal growth retardation [2, 6]. However, exact mechanism involving it still needed further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have illustrated that infertile PCOS patients present the impairment of endometrial receptivity and were vulnerable to undergo recurrent pregnancy loss, premature labour and fetal growth retardation [2, 6]. However, exact mechanism involving it still needed further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, continued adenoviral delivery of cyclin D3 to support normal decidualization in defect endometrium was flawed, because repeated administration can result in animal sickness and even lethal to pups before delivery [24]. Other common pharmacological options for hyperandrogenemia present in PCOS patients are involved in dexamethasone, metformin and flutamide [2]. Through incubating endometrial cells of normal cycling women, dexamethasone was verified to restore the impairment of a low-dose testosterone on endometrium, but had no effect on high dose.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 prerequisite factors for successful implantation are the em- bryo with implantation competency, the endometrium in receptive state, and the synchronized development of both the embryo and the endometrium [13]. It is generally accepted that endometrial receptivity is critical to successful pregnancy [14], it is a multifactorial process [15], and secondary infertility is a common initial symptom of IUAs [2]. The present study has revealed that vaginal administration of sildenafil citrate during FET in patients receiving resection of IUAs evidently improves their pregnancy outcomes, which can be viewed as a promising treatment for infertile women with endometrial insufficiency after FET.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is a common endocrine and reproductive syndrome that is frequently associated with obesity, insulin resistance, metabolic disorders, and cardiovascular risk factors [25][26][27][28]. The etiology of this syndrome remains largely unclear, but increasing evidence suggests that PCOS might be that of a complex multigenic trait in which environmental influences play an important role, such as organic compounds and heavy metals [29,30].…”
Section: Discussionmentioning
confidence: 99%